PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP KESADARAN HAK DAN KEWAJIBAN MAHASISWA GENERASI Z DI LINGKUNGAN KAMPUS - Annora Rama Evaretta; Teguh Sutriono; Suparmi Suparmi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This literature study examines the complex impact of social media use on Generation Z students' awareness of their rights and obligations on campus. As a generation that grew up with technology, Gen Z students use digital platforms intensively to express themselves, access information, and participate in social issues. Positively, social media functions effectively as an informal educational tool, with educational content on platforms like Instagram significantly enhancing students' understanding of academic rights and freedom of expression. Furthermore, social media encourages active student participation in campus activities and the courage to criticize policies. However, the findings also highlight significant challenges posed by social media use. High levels of entertainment can lead to a shift in social values, particularly toward a consumerist lifestyle, and reduce focus on academic responsibility. Social media becomes a space for the spread of hoaxes and polarization, with students often sharing information without verification, which negatively correlates with critical behavior and can decrease empathy and tolerance. The risk of slacktivism—symbolic engagement in the digital realm without concrete action—was also identified.